Phytase: application in food industry - Suhairin, Afinah; Abd. Manap, Mohd. Yazid; Meor Hussin, Anis Shobirin; Mustafa, Shuhaimi (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2010)
Phytates have been considered as a threat in human diet due to its antinutrients behaviour which known as strong chelators of divalent minerals such as Ca²+, Mg²+, Zn²+ and Fe²+. Phytic acid has a potential for binding positively charged proteins, amino acids, and/or multivalent cations or minerals in foods. The resulting complexes are insoluble, difficult for humans to hydrolyze during digestion, and thus, typically are nutritionally less available for absorption. The reduction of this phytates can be achieved through both enzymatic and non-enzymatic removal. Enzymatic degradation includes addition of either isolated form of wild-type or recombinant exogenous phytate-degrading enzymes microorganisms in the food matrix. Non-enzymatic hydrolysis of phytate occurred in the final food during food processing or physical separation of phytate-rich parts of the plants seed. The application of phytase with respect to breadmaking process, probiotics, animal feed supplement and transgenic crops are emphasised in this paper.